In vitro activity of soybean extract on cocoa disease pathogens (Erythricium salmonicolor and Marasmiellus scandens) and termite pest (Microtermes subhyalinus) - Yahaya Bukari; Silas W. Avicor; Godfred Awudzi; Michael K. Ainooson; Eric K. Asare; Ishmael Amoako-Attah (Cogent Food & Agriculture, 2022)
AbstractThis study evaluated the antifungal and insecticidal properties of soybean extract on Marasmiellus scandens (causal pathogen of white thread blight disease on cocoa), Erythricium salmonicolor (causal pathogen of pink disease of cocoa) and termite (Microtermes subhyalinus). Agar plate test was used to determine the inhibitory activity of the extract on mycelial growth of the pathogens while a contact toxicity bioassay was conducted on the termites. Extract of the soybean reduced mycelial growth in a dose-dependent pattern, with 20% of the extract attaining the highest inhibition. Percentage inhibition of 80.4 and 86.8 were recorded for E. salmonicolor and M. scandens, respectively after 7 days of incubation. The IC50 values ranged between 0.64–2.44% and 0.12–0.45% for E. salmonicolor and M. scandens respectively. However, activity of the extract on the termite was low, with an LC50 of 15.42% after 24 hours of exposure. The effect of the extract on the fungal pathogens indicates that it could be further explored towards the development of a plant-based control method against white thread blight and pink diseases of cocoa in Ghana.